INTERPROFESSIONAL LEARNING IMPACTS ON PROFESSIONAL DYNAMICS AMONG HEALTH PROFESSIONALS IN SOUTHEASTERN NIGERIA. - Elugwu, Chukwuemeka Henry; Idigo, Felicitas U.; Makata, Ngozi E.; Ugwu, Anthony C.; Ohagwu, Christopher C.; Eze, Joseph C.; Ikegwuonu, Nwamaka (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2023)
Assessment of the impact of interprofessional learning (IPL) on professional dynamics among healthcare professionals is very important for quality patient care management. The research design was a prospective cross-sectional descriptive study. It was conducted in various healthcare departments at Federal Medical Centres and Federal Teaching Hospitals in South-East of Nigeria having a sample size of 386 healthcare professionals. Validated questionnaire “Interprofessional Learning Dynamic Scale (IPLDS)” was used for this study. It contained 63 items with 2-sections: A and B. ‘A’ for socio-demographic data and ‘B’ for professionals’ relationship, knowledge, readiness, perception and attitude towards IPL. Data was collected through simple random sampling and analysed descriptively using Spearman rank correlation. Previous IPL experience showed significant positive relationship with radiographers’ ability to accommodate, collaborate, form teamwork, resolve conflict and communicate effectively with other healthcare professionals. This study reveals that previous interprofessional learning experience promotes positive group dynamics between radiographers and other healthcare professionals, promotes better understanding of one’s own and others’ roles. Level of education had negative significance with knowledge (rs = -0.192; p = 0.000), readiness, perception and attitude towards IPL (rs = -0.299; p = 0.000). Level of education were of great influence on radiographers’ relationship with other healthcare professionals. This study affirm that IPL experience proves to have more positive chances to strengthen team dynamics and prevent the transfer of disciplines negative stereotypes into the workforce.